Medical Liability in Cancer Care During COVID-19 Pandemic: Heroes or Guilty? - Barranco, Rosario; Messina, Carlo; Bonsignore, Alessandro; Cattrini, Carlo; Ventura, Francesco (Frontiers in Public Health, 2020)
Background: The COVID-19 outbreak rapidly became a public health emergency affecting particularly frail category as cancer patients. This led oncologists to radical changes in patient management, facing the unprecedent issue whether treatments in oncology could be postponed without compromising their efficacy. Purpose: to discuss legal implications in oncology practice during COVID-19 pandemic. Perspective: treatments delay is not always feasible in oncology where the timing often plays a key role and may impact significantly in prognosis. During COVID-19 pandemic, the oncologists were found between the anvil and the hammer, on the one hand the need to treat cancer patients aiming to improve clinical benefits, and on the other hand the goal to reduce the risk of COVID-19 infection avoiding or delaying immunosuppressive treatments and hospitals exposure. Therefore, two rising scenarios with possible implications in both criminal and civil law are emerging. Firstly, oncologists may be "accused" for having delayed or omitted the diagnosis and/or treatments with consequent worsening of patients’ outcome. Secondly, oncologists can be blamed for having exposed patients to hospital environment considered at risk for COVID-19 transmission. Conclusions: During COVID-19 pandemic clinical decision making should be well balanced through a careful examination between clinical performance status, age, co-morbidities, aim of the treatment and the potential risk of COVID-19 infection in order to avoid the risk of suboptimal cancer care with potential legal repercussion. Moreover, all cases should be discussed in oncology team or in tumor board in order to share the best strategy to adopt case by case.